Inferred Switching Behavior in Response to Re-entry of Uber and Lyft: A Revealed Study in Austin, TX - Xuan Di; Tayo Fabusuyi; Chris Simek; Xi Chen; Robert C. Hampshire (Findings)
In May 2016, Uber and Lyft suspended services following the defeat of Proposition 1 in Austin, TX. In response, several ridesourcing services entered the market. This paper provides information on the individuals most likely to switch back to Uber or Lyft after service restoration using estimated indifference bands. We hypothesize that people will not switch back unless a given trip’s cost saving is beyond a positive threshold due to boundedly rational behavior. The study revealed, among others, that those who use TNC for social purposes, have lower indifference bands and are more likely to switch to Uber or Lyft.